Elder Abuse—The Current State of Research in South Africa - Kotzé, Carla (Frontiers in Public Health, 2018)
Objectives: The concern about elder abuse increases as the global population ages. Elder abuse is a global public health, human rights and criminal justice problem that goes beyond socioeconomic classes and regions. It remains understudied, especially in developing countries with limited resources. It is therefore timely to do a review of the available research on elder abuse in South Africa, to be able to address the gaps in the research with future projects. Methods: Publications were identified from PubMed, MEDLINE, PsychINFO, Sabinet, Africa-Wide Information, CINAHL, E-Journals, Family & Society Studies Worldwide, PsycARTICLES, Criminal Justice Abstracts and Social Work Abstracts. Fourteen articles on elder abuse in South Africa were selected for further review. This paper provides a narrative review of elder abuse in South Africa and is not a systematic review. Discussion: South Africa is a multicultural nation, plagued by HIV/AIDS, poverty and the remaining effects of the legacy of apartheid. This background sets the stage for categories of abuse that are unique to the country that are highlighted in this review. The available research on elder abuse is very limited and no reliable data about the prevalence of elder abuse in South Africa could be found. Conclusions: There is a clear need for more longitudinal research about all aspects of elder abuse in South Africa. To improve future research efforts consensus has to be reached about a universal operational definition of abuse and an elder abuse instrument with a clear cut-off for definite elder abuse.